2021
DOI: 10.15847/obsobs15120211692
|View full text |Cite
|
Sign up to set email alerts
|

Politicians self-representation on instagram: the professional and the humanized candidate during 2019 spanish elections

Abstract: Instagram has become an important tool to contact the audiences both in commercial and political communication. Of special interest is the use of this social network by politicians, who can use the image to portray a humanized version of themselves: it is not the candidate but the person who is talking to citizens through impacting images posted on their personal profiles. The present study posits that Instagram is a key tool for self-representation. This paper offers a specific study about the use of Instagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Instagram maximizes the ability of candidates to selfrepresent and can thus easily lead to their spectacularization. In this social network, candidates can make themselves known professionally or from a personal point of view through the deliberate selection of the elements they include in their images, such as symbols or location (Bellido-Pérez & Gordillo-Rodríguez, 2022;Gordillo-Rodríguez & Bellido-Pérez, 2021). Instagram's visual nature is the key to its success among parties and candidates at the international level (Lalancette & Raynauld, 2020) because it allows these users to build an image of leadership based on positive attributes such as honesty, sincerity, credibility, kindness, or leadership ability (Lalancette & Raynauld, 2019).…”
Section: Political Spectacularization On Instagrammentioning
confidence: 99%
“…Instagram maximizes the ability of candidates to selfrepresent and can thus easily lead to their spectacularization. In this social network, candidates can make themselves known professionally or from a personal point of view through the deliberate selection of the elements they include in their images, such as symbols or location (Bellido-Pérez & Gordillo-Rodríguez, 2022;Gordillo-Rodríguez & Bellido-Pérez, 2021). Instagram's visual nature is the key to its success among parties and candidates at the international level (Lalancette & Raynauld, 2020) because it allows these users to build an image of leadership based on positive attributes such as honesty, sincerity, credibility, kindness, or leadership ability (Lalancette & Raynauld, 2019).…”
Section: Political Spectacularization On Instagrammentioning
confidence: 99%
“…El análisis de los contenidos de las páginas sociales de figuras políticas se ha convertido en una vía primordial de investigación de datos en comunicación política (Gelpi, 2018), considerando que "la individualidad del candidato político se postula cada vez más como imagen de marca" (Pérez-Curiel y Limón-Naharro, 2019, p. 57), a la que se suman los atributos de autenticidad, pasión y fascinación como claves de su estrategia (Rodríguez, 2021). En este sentido, trabajos precedentes refuerzan la preeminencia de lo visual en la percepción de la arena política, donde los líderes "utilizan los vídeos y fotografías que comparten para humanizar su figura" (Quevedo-Redondo y Portalés-Oliva, 2017, p. 916).…”
Section: Rschunclassified
“…A substantial body of literature in recent years has applied the method of visual framing in political communication (Brantner et al, 2011; Farkas and Bene, 2021; Gordillo-Rodriguez and Bellido-Perez, 2021; Grabe and Bucy, 2009; Russmann and Svensson, 2016; Steffan, 2020). Gordillo-Rodriguez and Bellido-Perez (2021) explored the self-presentation of the five main Spanish political candidates on Instagram in order to reveal whether the candidate shows himself on Instagram in a predominantly personal and private context or in a more professional and political way. The researchers followed Goffman’s (1959) principles to explain candidates’ self-representation tactics on Instagram, which assert that candidates represent the best version of themselves or, at least, an image corresponding to what citizens may consider an ideal candidate.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These studies have illustrated that the use of social media platforms during election campaigns attracts higher levels of audience attention and interest. It was also revealed that when political leaders share more emotional and private content, they create positive impressions on citizens (Gordillo-Rodriguez and Bellido-Perez, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation